Social Media in Higher Education: Case Studies, Reflections and Analysis - Rowell, Chris (Editor) (Open Book Publishers, 2019)
"How does social media affect working life in Higher Education? How are universities harnessing its power to aid student learning? This innovative collection brings together academics and those working in professional services to examine these questions and more. The diverse and expert contributors analyse the many ways social media can be used to enhance teaching and learning, research, professional practice, leadership, networking and career development. The impact of social media is evaluated critically, with an eye both to the benefits and the problems of using these new forms of digital communication. This is the first volume to give such detailed attention to this area of high interest. Its innovative approach extends to its creation, with contributors found via their presence on Twitter. The short and impactful chapters are accessible while retaining an academic focus through their application of relevant learning theory and educational context. Social Media and Higher Education is essential reading for any professional working in higher education, including lecturers teaching education courses. It is also significant for researchers looking at more recent developments in higher education and what it means to work in a modern higher education environment."